2012
DOI: 10.1115/1.4004858
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coolant Flow Rate on Aero-Thermal Performance of a Rotor Blade Cascade With Endwall Film Cooling

Abstract: This paper investigates the influence of coolant injection on the aerodynamic and thermal performance of a rotor blade cascade with endwall film cooling. A seven blade cascade of a high-pressure-rotor stage of a real gas turbine has been tested in a low speed wind tunnel for linear cascades. Coolant is injected through 10 cylindrical holes distributed along the blade pressure side. Tests have been preliminarily carried out at low Mach number (Ma2is = 0.3). Coolant-to-mainstream mass flow ratio has been varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Measurements highlighted that for this positioning, the impact on losses was negligible because the coolant flow did not interact with the horseshoe vortex and passage vortex generation, but instead it only energised the platform boundary layer. As also shown in [21,24], testing different hole patterns, still located inside of the passage, the platform flow field is mainly influenced by the passage vortex and its interaction with coolant flow. When the injected cool air is not captured by the vortex, only the end wall crossflow acts, and secondary flows are barely affected.…”
Section: Aerodynamics and Heat Transfer Phenomena In Film-cooled Roto...mentioning
confidence: 75%
See 3 more Smart Citations
“…Measurements highlighted that for this positioning, the impact on losses was negligible because the coolant flow did not interact with the horseshoe vortex and passage vortex generation, but instead it only energised the platform boundary layer. As also shown in [21,24], testing different hole patterns, still located inside of the passage, the platform flow field is mainly influenced by the passage vortex and its interaction with coolant flow. When the injected cool air is not captured by the vortex, only the end wall crossflow acts, and secondary flows are barely affected.…”
Section: Aerodynamics and Heat Transfer Phenomena In Film-cooled Roto...mentioning
confidence: 75%
“…Indeed, the arrangement of cooling holes within the platform is a key issue. At Bergamo University a research activity was carried out over some years to design and verify the introduction of discrete holes at different locations: close to the pressure side, to exploit the passage vortex cross flow [21], along the inter-platform gap [24] and rear in the passage, downstream the throat [26]. The aim was always to effectively protect specific regions of the platform particularly exposed to hot gas contact, while, in the meantime, considering the constraints imposed by the secondary air system.…”
Section: Blade Cascade Researchesmentioning
confidence: 99%
See 2 more Smart Citations
“…They determined that rotor platform cooling has minimal effects on the suction side and trailing edge of the rotor. Barigozzi et al [6] also suggested that this is due to the coolant flow from the hub disk being captured by the rotor hub passage vortex which moves the coolant away from the rotor endwalls. Suryanarayanan et al [12,13] showed using pressuresensitive paint that coolant supplied by purge flow did not provide sufficient coolant to the pressure side of the rotor.…”
Section: Introductionmentioning
confidence: 99%